2016
DOI: 10.1186/s12968-017-0411-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimized CEST cardiovascular magnetic resonance for assessment of metabolic activity in the heart

Abstract: BackgroundPrevious studies have linked cardiac dysfunction to loss of metabolites in the creatine kinase system. Chemical exchange saturation transfer (CEST) is a promising metabolic cardiovascular magnetic resonance (CMR) imaging technique and has been applied in the heart for creatine mapping. However, current limitations include: (a) long scan time, (b) residual cardiac and respiratory motion, and (c) B0 field variations induced by respiratory motion. An improved CEST CMR technique was developed to address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 25 publications
3
44
0
Order By: Relevance
“…In the infarcted myocardium of large animals, resting creatine CEST contrast has been shown to be reduced by 50-70% compared with remote healthy myocardium. 28,29 While the reduction in creatine CEST contrast among obese adults in this study was below that observed in infarcted tissue in prior studies, it closely resembled the relative reduction in creatine CEST contrast in border zone tissue seen in miniature pigs by Zhou et al 29 However, the CEST contrast values measured in healthy controls in our study were lower than those observed in healthy myocardium in both prior studies, despite similar cardiomyocyte creatine concentrations between species. It is important to note differences in how the CEST-weighted images were acquired between studies.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In the infarcted myocardium of large animals, resting creatine CEST contrast has been shown to be reduced by 50-70% compared with remote healthy myocardium. 28,29 While the reduction in creatine CEST contrast among obese adults in this study was below that observed in infarcted tissue in prior studies, it closely resembled the relative reduction in creatine CEST contrast in border zone tissue seen in miniature pigs by Zhou et al 29 However, the CEST contrast values measured in healthy controls in our study were lower than those observed in healthy myocardium in both prior studies, despite similar cardiomyocyte creatine concentrations between species. It is important to note differences in how the CEST-weighted images were acquired between studies.…”
Section: Discussionsupporting
confidence: 81%
“…Also, both prior studies were performed at field strengths of 3 T (versus 1.5 T in the current study) using single‐shot acquisitions. In the study performed by Zhou et al the use of single‐shot readouts enabled multiple points along a Z spectrum to be acquired in a single breath hold . In our preliminary studies, we observed significant motion artifacts when using a single‐shot readout to acquire an end‐diastolic frame, even when using a centric‐out encoding scheme.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The chemical exchange saturation transfer (CEST) technique has been developed to quantify metabolites and macromolecules 63)64)65). In a recent study, CEST was able to map the creatine distribution within the myocardium to evaluate the metabolic activity in an animal model,66) and an optimized in vivo cardiac CEST sequence that maps free creatine in myocardial tissue, with a markedly reduced scan time by 10-fold and improved motion registration and signal calculation, has been developed 67). The feasibility of the sequence has been tested against LGE imaging as a reference in a porcine myocardial infarction model, and the sequence has been applied in a patient with chronic myocardial infarction.…”
Section: Imaging and Characterization Of The Myocardiummentioning
confidence: 99%